THE USAGE OF CHIA SEEDS IN THE PRODUCTION OF YOGURT DESSERTS FOR ATHLETES - N. Tkachenko; Z. Podolian (Zernovì Produkti ì Kombìkorma)
A healthy lifestyle today is inextricably linked to proper nutrition. At the forefront of the struggle for beauty, health and youth are superfoods - products with unique biological characteristics, which include chia seeds. The paper provides an analysis of the chemical composition, properties, nutritional and biological value of chia seeds. It is shown that chia seeds are indispensable in the nutrition of athletes: due to their rare gel-forming properties, rich chemical composition and low calorie content, chia seeds are able to turn any drink (including yogurt) into a biologically active product that replenishes energy expenditure, gives strength and endurance, is able to build muscle mass, get rid of excess fat if whole grains are used in the product or help maintain current weight if crushed seeds are used in the product. The microflora of chia seeds before heat treatment and after infusing its grains in milk at temperatures of +66±1,+76±1 and +86±1?С for 31±1 min was studied. It is recommended to infuse chia seeds in the prepared yogurt base at a temperature of +86±1?С for 31±1 min for the preparation of yogurt desserts for athletes intended for weight loss (ratio of chia seeds: yogurt base during infusing – 1:4), cool to the fermentation temperature – +40±1?С, and then mix with the yogurt base prepared for fermentation at a ratio of yogurt base: infused chia seeds of 3:1. The efficiency of pasteurization was determined in samples of yogurt base enriched with crushed chia seeds, prepared from milk of extra and higher grades. It is shown that high pasteurization efficiency (>99.98%) is achieved by pasteurizing a yogurt base enriched with crushed chia seeds at a temperature of +90…95?С for 10…20 min. It is recommended to add crushed chia seeds (particle size 0.5 mm) to the yogurt base during the process of normalization by mass fraction of DSMR together with KSB-UF-75 for the preparation of a yogurt base with crushed chia seeds for the production of yogurt desserts for athletes intended for weight loss and for maintaining current weight, respectively. Technological schemes for the preparation of a yogurt base with whole and crushed chia seeds for the production of yogurt desserts for athletes intended for weight loss and for maintaining current weight, respectively, are presented.